PENDEKATAN PAKEM DALAM PEMBELAJARAN IPA DI MIN RUKOH - Azhar (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2019)
Abstract In the teaching and learning process is inseparable from the ways and methods appropriate for teaching and learning activities so that learning objectives are achieved, especially in science learning. The objectives of this study are: (1) to find out the activities of teachers and students in learning, (2) to find out students' responses by applying the PAKEM approach in science learning. This type of research is a classroom action research (CAR), this learning consists of 2 cycles, the subjects in this study were VA MIN Rukoh class students, amounting to 42 people. The instruments used were teacher and student observation sheets, tests, and questionnaires. Data obtained about the activities of teachers and students, student responses were analyzed and described using the percentage formula. The results obtained from this study are (1) The activities of teachers and students in science and learning activities have reflected learning using the PAKEM approach and improving student learning outcomes. Teacher activities in managing learning using the PAKEM approach in cycle I and cycle II have increased by the percentage an average of 77.77% in the first cycle and 96.29% in the second cycle, the activity of students in participating in learning also increased with an average percentage of 84.84% in the first cycle and 96.96% in the second cycle (2 ) The response of students to teaching and learning activities using the PAKEM approach generally expresses happiness and feels interested in following the next lesson. Keywords: Learning Strategies, PAKEM Approach, Science Abstrak Dalam proses belajar mengajar tidak terlepas dari cara dan metode yang sesuai untuk kegiatan belajar mengajar sehingga tercapai tujuan pembelalajaran, khusunya pada pembelajaran IPA . Adapaun tujuan penelitian ini adalah: (1) untuk mengetahui aktivitas guru dan siswa dalam pembelajaran, (2) untuk mengetahui respon siswa dengan penerapan pendekatan PAKEM dalam pembelajaran IPA . Jenis penelitian ini adalah penelitian tindakan kelas (PTK), pembelajaran ini yang terdiri dari 2 siklus, subjek dalam penelitian ini adalah siswa kelas VA MIN Rukoh yang berjumlah 42 orang. Instrument yang digunakan adalah lembar observasi guru dan siswa, tes, dan angket. Data yang diperoleh tentang aktivitas guru dan siswa, respon siswa dianalisis dan didesksripsikan dengan rumus persentase. Hasil yang diperolehdari penelitian ini adalah (1) Aktivitas guru dan siswa dalam kegiatan belajar mengajar IPA sudah mencerminkan pembelajaran dengan pendekatan PAKEM dan meningkatkan hasil belajar siswa, Aktivitas guru dalam mengelola pembelajaran dengan menggunakan pendekatan PAKEM pada siklus I dan siklus II mengalami peningkatan yaitu dengan persentase rata-rata 77,77 % pada siklus I dan 96,29 % pada siklus II, Aktifitas siswa dalam mengikuti pembelajaran juga mengalami peningkatan yaitu dengan persentase rata-rata 84,84 % pada siklus I dan 96,96 % pada siklus II (2) Respon siswa terhadap kegiatan belajar mengajar dengan menggunakan pendekatan PAKEM pada umumnya menyatakan senang dan merasa tertarik untuk mengikuti pembelajaran berikutnya. Kata Kunci: Strategi Pembelajaran, Pendekatan PAKEM, IPA